A map of the fractal structure of high-tech dynamics across EU regions - Ariel L. Wirkierman; Tommaso Ciarli; Maria Savona (United Nations University (UNU), Maastricht Economic and Social Research Institute on Innovation and Technology (UNU-MERIT), 2021)
The paper provides a novel, theoretically driven map of EU regional asymmetries, based on the shares and dynamics of high-tech employment and wages, as well as the structure of inter-regional Input-Output relations at the EU NUTS-1 regional level. We use data from EUROSTAT and the EU-REGIO database to perform a trade-aware shift-share analysis coupled with a hierarchical clustering. We show that EU regions present a fractal structure of asymmetries, i.e. the emergence of core-periphery relations at progressively smaller scales, in relation to both spatial and trade dimensions. We identify regional clusters labelled 'consolidated core', 'declining core', 'emerging cities', 'declining peripheries' and 'CEE factories', and we show that there is a polarising dynamics between driving and follower clusters, drawing implications for EU cohesion policy.
Keywords: R11; O30; C38; 330; Regional high-tech employment; Regional wage rate differentials; Cluster Analysis; European cohesion policy